Pengaruh Kepemimpinan Demokratis, Konflik Kerja dan Beban Kerja terhadap Kinerja Karyawan Pada Kayumanis Ubud Private Villa & Spa - Maharani, Ni Luh Novia; Astrama, I Made; Ary Pratiwi, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the influence of democratic leadership, work conflict and workload on employee performance at Kayumanis Ubud Private Villa & Spa. The research method used is quantitative. The location of the Kayumanis Ubud Private Villa & Spa study with the total population in this study is all employees of Kayumanis Ubud Private Villa & Spa which amounted to 96 people because the population was less than 100 so it used the entire population or often also called using saturated samples. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. Based on the results of the study, it was found that democratic leadership has a significant positive effect on the performance of employees of Kayumanis Ubud Private Villa & Spa. Work conflict has a significant negative effect on the performance of employees of Kayumanis Ubud Private Villa & Spa. Workload has a significant negative effect on the performance of Kayumanis Ubud Private Villa & Spa employees. Democratic leadership, work conflict, and workload simultaneously have a significant positive effect on the performance of Kayumanis Ubud Private Villa & Spa employees. Advice that can be given is that pimpian Kayumanis Ubud Private Villa & Spa has a high initiative in providing motivation, support and positive direction to all employees.